Paulhan Before Blanchot: From Terror to Letters Between the Wars - Steven Ungar (Studies in 20th & 21st Century Literature, 1985)
Readers of Blanchot's writings make up at least three generations which, in turn, point to the relevance of locating his practices of modernity in relation to literary and social history. An initial inquiry sets Blanchot's early writings against those of Jean Paulhan in the 1936 period of the Popular Front, rather than in the early part of the Second World War, as is commonly supposed. By pushing the early writings back to the period between the wars, we can better understand the place of political concerns in Blanchot's subsequent narratives and essays.
Keywords: Blanchot; modernity; literary history; social history; Jean Paulhan; Popular Front; Second World War; politics